The use of the material composition of rocks for the correlation of the stratigraphic units of the Ukrainian Shield - Usenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
In the Precambrian, the material composition of the rock complexes changed regularly. This fact is established for all cratons of the world. The level emerging today in the granulite blocks of the Ukrainian Shield was located in the Archean-Paleoproterozoic at the depth of the middle and lower crust. Therefore, the processes running under the near-solidus conditions (the introduction of melts, fluids, metasomatic substitutions, etc.) played the determining role in their structure. Geological manifestations characteristic of the upper crust, including sediment the accumulation and folding, occurred at a level eroded in subsequent geodynamic processes. To correlate the stratigraphic units of granulite blocks of the Shield, we can use the material composition of metamorphic and igneous complexes.